Escape from Milan: Honorius and the displacement of the imperial court (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
Between fall and winter 402 the imperial court moved from Milan to Ravenna. Zosimus and Procopius are known to have shown the strategic choice of Honorius about Ravenna, the relevance of which had been growing since the time of the principate when it was the seat of the military fleet in the Adriatic Sea. Archaeological evidence, however, does not confirm continuity between the military port and the regia civitas. Ravenna during the time of Honorius was quite different from the past, and it was badly affected by the dismantling of the fleet which has not been attested since mid 3rd century. Even the new reading of a milestone from Campiano (AE 1975, 402) does not allow to hold this document as an evidence of a not attested unchanged persistence in the city life of Ravenna.
Keywords: Ravenna; classis praetoria; Honorius; Zosimus; Procopius